DETERMINANTS OF YOUTH-PRENEURIAL READINESS FOR SOCIAL ENTREPRENEURSHIP: PROPOSING A CONCEPTUAL MODEL - Nur Syifaa Athirah Mohd Said; Nur Izzati Ab Ghani; Zanariah Mohd Nor; Farah Roslan; Muhamad Nasyat Muhamad Nasir, (ADVANCED INTERNATIONAL JOURNAL OF BUSINESS, ENTREPRENEURSHIP AND SME'S (AIJBES), 2025)
Social entrepreneurship has increasingly been recognized as a dynamic approach for addressing various social, environmental, and economic issues. Despite the growing prominence of social entrepreneurship, Malaysia is experiencing a noticeable disparity in youth participation in this field. This conceptual study aims to examine the factors influencing the readiness of young individuals to participate in social entrepreneurship, with the objective of empowering both youth and the broader community. Previous researches have established that critical factors such as empathy, prior experience, entrepreneurship education, and self-efficacy are instrumental in shaping the readiness of youth to engage in social entrepreneurship. This study is expected to provide significant insights, which will serve as the foundation for developing a comprehensive framework specifically designed for Malaysian youth. It is intended to clarify the complex dynamics involved, revealing both the facilitating and inhibiting factors affecting Malaysian youth’s participation in social entrepreneurship. This framework will provide policymakers with essential insights to foster a more supportive environment for promoting social entrepreneurship among Malaysian youth. These efforts are ultimately aligned with the broader goals set forth in the National Entrepreneurship Policy 2020-2030, which seeks to position Malaysia as a leading example of entrepreneurial excellence by the year 2030.